2023
DOI: 10.3390/vaccines11010104
|View full text |Cite
|
Sign up to set email alerts
|

Talking about the Vaccine after the Pandemic: A Cross-Sectional Study among Youth in Turkey and Ethical Issues

Abstract: Examining the factors that affect the vaccination rate among young people in an ethical frame can support vaccination promotion. Therefore, this study will elaborate, through an ethical lens, on young people’s hesitation about and decisions regarding getting vaccinated. The cross-sectional study was conducted with 2428 people aged 15–30 in Turkey in June 2022. The questionnaire included the following subtitles: psycho-social situation, health services and health policies, COVID-19 vaccine, and predictions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(93 reference statements)
0
2
0
1
Order By: Relevance
“…Encouragingly, a recent study in Italy reported a vaccination rate of 87.3% among school-going adolescents [ 95 ]. Additionally, in Turkey, the vaccination rate among youths was 80% [ 96 ]. Alongside this in Kersa, Ethiopia, 86% of adolescents stated they would seek vaccination once available [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, a recent study in Italy reported a vaccination rate of 87.3% among school-going adolescents [ 95 ]. Additionally, in Turkey, the vaccination rate among youths was 80% [ 96 ]. Alongside this in Kersa, Ethiopia, 86% of adolescents stated they would seek vaccination once available [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this in Kersa, Ethiopia, 86% of adolescents stated they would seek vaccination once available [ 84 ]. In Turkey, the youths wanted to be vaccinated to protect their health as well as the health of their families and relatives [ 96 ]. In Brazil, a recent study reported that 88.7% of caregivers wanted their children to be vaccinated while 77.6% of parents in China wanted their children to be vaccinated against COVID-19 [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Özdinç ve ark. tarafından yapılan çalışmada gençler arasındaki aşılama oranını etkileyen faktörler; önerilen aşılar hakkında doğru ve yeterli bilgiye sahip olmak, kendilerini, ailelerini ve yakınlarını korumak iken aşı olmama nedenlerinin başında aşı içeriğine veya aşının üretildiği ülkeye güvenmemek olduğu bulunmuştur (24).…”
Section: Gereç Ve Yöntemler çAlışmanın Tipi öRneklemunclassified